The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1111/1467-9604.12012
|View full text |Cite
|
Sign up to set email alerts
|

Secondary school transition for children with special educational needs: a literature review

Abstract: Successful transition from primary to secondary school is important for psychosocial well‐being. Children with special educational needs (SEN) may face additional complexities at transition, although the impact of this process on children's psychosocial adjustment has been underexplored. The article aims to review systematically the literature exploring the impact of transition on the concerns and psychosocial adjustment of children with SEN in comparison to typically developing children. Published studies wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
71
0
9

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(82 citation statements)
references
References 38 publications
2
71
0
9
Order By: Relevance
“…Since Hughes et al (2013) conducted their review, a number of additional studies have been published finding similar results. First, Akos et al (2015) reported less growth in both maths and reading during the transition year for SEN students despite having the largest year-to-year growth in the year prior to the changeover.…”
Section: The Effects Of the Transition To Secondary Education On Emotmentioning
confidence: 77%
See 1 more Smart Citation
“…Since Hughes et al (2013) conducted their review, a number of additional studies have been published finding similar results. First, Akos et al (2015) reported less growth in both maths and reading during the transition year for SEN students despite having the largest year-to-year growth in the year prior to the changeover.…”
Section: The Effects Of the Transition To Secondary Education On Emotmentioning
confidence: 77%
“…In a systematic review examining the effects of the school transition for children with SEN, Hughes et al (2013) investigated psychosocial functioning including internalizing functioning, self-concept, self-esteem, self-confidence, externalizing functioning, and social functioning. They identified key findings of a higher likelihood of victimization and bullying, poorer social adjustment (i.e., loneliness) and lower levels of perceived social support relative to typically developing children.…”
Section: The Effects Of the Transition To Secondary Education On Emotmentioning
confidence: 99%
“…Whilst student participants in Jindal-Snape et al 's study (2006) found the transition from primary to secondary school to be a mostly positive experience as well, they also expressed their desire for true inclusion at school. Hughes, Banks, and Terras (2013) found that students with ASD were more stressed about bullying and social interactions in the high school environment than other students with disabilities. In contrast, Mandy et al (2015) suggested that there was no indication of a rise in the difficulty for students with ASD through the transition process.…”
Section: Introductionmentioning
confidence: 94%
“…Limited focus on the impact of primary-secondary school transition on AC and MHF of students with disabilities Few studies have considered the impact of transition to secondary school on AC and MHF of students with disabilities [34]. Students with learning disabilities have been reported to experience reductions in AC [35], while their typically developing counterparts show increased scores.…”
Section: Introductionmentioning
confidence: 99%